New arylsparteine derivatives as positive inotropic drugs. (1st January 2017) - Boido, Vito; Ercoli, Marcella; Tonelli, Michele; Novelli, Federica; Tasso, Bruno; Sparatore, Fabio; Cichero, Elena; Fossa, Paola; Dorigo, Paola; Froldi, Guglielmina
Abstract: Positive inotropic agents are fundamental in the treatment of heart failure; however, their arrhythmogenic liability and the increased myocardial oxygen demand strongly limit their therapeutic utility. Pursuing our study on cardiovascular activities of lupin alkaloid derivatives, several 2-(4-substituted-phenyl)-2-dehydrosparteines and 2-(4-substituted-phenyl)sparteines were prepared and tested for inotropic and chronotropic activities on isolated guinea pig atria. Four compounds (6b, 6e, 7b, and7f ) exhibited significant inotropism that, at the higher concentrations, was followed by negative inotropism or toxicity. Compound7e (2-(4-tolyl)sparteine) exhibited a steep dose-depending inotropic activity up to the highest concentration tested (300 µM) with an E max of 116.5 ± 3.4% of basal force, proving less potent but much more active in comparison to the highest concentrations tested of digoxin and milrinone having E max of 87.5 ± 3.1% and 52.2 ± 1.1%, respectively. Finally, docking studies suggested that the relevant sparteine derivatives could target the sigma-1 receptor, whose involvement in cardiac activity is well documented.